Transmembrane formins as active cargoes of membrane trafficking - Cvrčková, Fatima; Ghosh, Rajdeep; Kočová, Helena (Journal of experimental botany, 2024)
Formins are a large, evolutionarily old family of cytoskeletal regulators whose roles include actin capping and nucleation, as well as modulation of microtubule dynamics. The plant class I formin clade is characterized by a unique domain organization, as most of its members are transmembrane proteins with possible cell wall-binding motifs exposed to the extracytoplasmic space-a structure that appears to be a synapomorphy of the plant kingdom. While such transmembrane formins are traditionally considered mainly as plasmalemma-localized proteins contributing to the organization of the cell cortex, we review, from a cell biology perspective, the growing evidence that they can also, at least temporarily, reside (and in some cases also function) in endomembranes including secretory and endocytotic pathway compartments, the endoplasmic reticulum, the nuclear envelope, and the tonoplast. Based on this evidence, we propose that class I formins may thus serve as 'active cargoes' of membrane trafficking-membrane-embedded proteins that modulate the fate of endo- or exocytotic compartments while being transported by them.
Keywords: formin; biotic interactions; Plant Proteins; cytokinesis; Protein Transport; tonoplast; Actin; membránové proteiny; cell growth; rostlinné proteiny; transport proteinů; plasmalemma; forminy; microtubules; Membrane Proteins; exocytosis; buněčná membrána; endocytosis; Formins; Cell Membrane